Synthesis and Characterization of a New N"-[(1Z,2E)-2- (Hydroxyimino)-1-phenylpropylidene]-N"'-[(1E)-phenylmethylene]thiocarbonohydrazide and its Complexes with Co(II), Ni(II) and Cu(II) - Dilip C. Sawant; A. Venkatchallam; R. G. Deshmukh (E-Journal of Chemistry)
Synthesis and characterization of a new N"-[(1Z,2E)-2- (Hydroxyimino)-1-phenylpropylidene]-N"'-[(1E)-phenylmethylene]thiocarbonohydrazide and its metal complexes with Co(II), Ni(II) and Cu(II) metal ions. The ligand synthesis and characterization is reported for first time. The complexes of divalent metal ions were synthesized in 1:2 molar proportion using ethanol as solvent. The ligands as well as its metal complexes were characterized using various physicochemical techniques such as elemental analysis, spectral and magnetic measurements and electrical conductivity measurements in case of the metal complexes only. The data for the metal complexes reveals that they may be represented by ML2. The metal complexes show interesting features of coordination structure.